Strategy and Models of Buildings Maintenance - a Literature Survey - Plebankiewicz, Edyta; Grącki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article comprehensive insights into the field of building maintenance, emphasizing the importance of keywords, collaborative efforts among authors, and the evolving research landscape are provided. The study conducts a thorough literature review using Scopus as a search engine, employing the full-counting method for authorship, and VOSviewer software for bibliometric analysis.
Keywords: building maintenance; university building; cost; renovation